SIFAT FISIK DAN KIMIA EDIBLE FILM PATI UMBI GADUNG PADA BERBAGAI KONSENTRASI - Mohammad Deden; Abdul Rahim; Asrawaty Asrawaty (Jurnal Pengolahan Pangan, 2020)
Today, the use of synthetic polymers as plastics has an important role in the economy of modern industrial society. Plastic packaging is often used as a food packaging material. However, the use of plastics can pollute the environment, because plastic is difficult to degrade naturally. One alternative to replacing the use of conventional plastics as food packaging is biodegradable plastic called edible film. The use of gadung tuber starch as a raw material for making edible films will not disturb food stability, because gadung is not consumed such as rice, corn and cassava. Gadung tubers are very good for edible film polymer materials containing high carbohydrates. Aim to determine the physical and chemical properties of the edible film starch of gadung tubers at various concentrations. The conclusion is that the optimum conditions for making edible films are good at 6% starch concentration with KA 11.50% and an average thickness of 0.13 mm.